(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
In present day world, mobile banking has emerged as a winner among various banking services. The major concern for mobile banking is its security. Since present authentication methods such as passwords, OTPs do not offer high level of security, there is always a risk of fraudulent attacks. To avoid this risk, reliable authentication procedures must be used. Biometric serves the purpose of reliable authentication mechanism. The paper gives the overview and quantitative comparative analysis of various physiological and behavioral biometric techniques that can be used in mobile banking. Various criteria that have been used for analysis are uniqueness, universality, permanence, circumvention, performance, and collectability and acceptability.